(3efgLjI GYOGO GdHMK GdYdej (B:s (3HcGdhQjhS(B- (3eGLSJjQ (B- (3OcJhQGg (B/s - (3YfGjI, ZGRjs ((3YeGf(B: s (3OGQ GdefGgL ddfTQ h GdJhRjY(B, s, 2008)
(3ebOeI Yf fTCI h GgejI efgfL GdHMK GdYdej eY JfGhd ebOeI JGQjNjI Yf GgejI h fTCI GdHMK GdYdej h GNjQG EYOGO HMK GdeNWhWI(B.s
(3eQGLY U(B.265s
Keywords: (3GdHMKs; (3WQb GdHMKs